On resurfacing a case for a cultural renaissance. - Huang, Angelito Junior (Espasyo : Journal of Philippine Architecture and Allied Arts, 2014)
Globalization and the advancement of technology have made the world smaller. Boundaries that define nations and nationalities have blurred and the resulting sense of displacement has undermined assumptions of identity and conversely, made the search for identity more urgent. This study investigates the dialogue between the contemporary arts and architecture through the lens of the Filipino culture as a way to recapture and bring to the surface the contemporary identity of Filipinos and the Philippines. The Philippines, as a culture of hybrid and regional identities, has long struggled to make sense of the Contemporary in a largely Traditional society. This study proposes the design and planning of a new Centre for Contemporary Arts in Manila to bring the diverse artistic activities of the country into focus. It intervenes at interface between the Traditional and the Contemporary, which bridges the gap between the two, thus heralding a Cultural Renaissance and help generate a sense of contemporary nationalism.